Incidencia del clima organizacional en el liderazgo del personal administrativo de la empresa Agroaéreo S.A, año 2023 - Vásquez Pérez , Victoria Concepción (2024)
This research project focuses on the "Impact of the Organizational Climate on the Leadership of Administrative Staff" in the company Agro Aéreo S.A., dedicated to the agricultural sector. The interrelationship between organizational climate and leadership is a key factor for the efficiency of work teams in a dynamic business environment. The research was carried out in depth evaluating the organizational climate in the company Agro Aéreo S.A., considering factors such as internal communication, motivation, teamwork and job satisfaction. The impact of these elements on the leadership role of administrative staff and, therefore, on the company's performance was examined. The results found in the survey show the clear incidence that the lack of efficiency is due to the effect of demotivation, on the part of the bosses, finding that 33%, while the collaborators indicated that their leaders most of the time have an appearance of a democratic leader, this being represented by 31%. In addition, it is considered that changes of immediate managers generate an effect on low work performance of 50%, communication between heads of areas and their collaborators was 43%, mentioning the lack of effective communication